Differential distribution and prognostic value of CD4+ T cell subsets before and after radioactive iodine therapy in differentiated thyroid cancer with varied curative outcomes - Shi, Zhi-Yong; Zhang, Sheng-Xiao; Li, Cai-Hong; Fan, Di; Xue, Yan; Cheng, Zhe-Hao; Wu, Li-Xiang; Lu, Ke-Yi; Wu, Zhi-Fang; Li, Xiao-Feng; Liu, Hai-Yan; Li, Si-Jin (Frontiers in Immunology, 2022)
Differentiated thyroid cancer is the most frequently diagnosed endocrine tumor. While differentiated thyroid cancers often respond to initial treatment, little is known about the differences in circulating immune cells amongst patients who respond differently. A prospective study of 39 patients with differentiated thyroid cancer was conducted. Serum thyroglobulin levels and thyroid and immunological functions were tested before and after radioactive iodine treatment (RAIT). Efficacy assessments were performed 6 to 12 months after radioactive iodine treatment. Most patients showed an excellent response to radioactive iodine treatment. Before radioactive iodine treatment, the excellent response group had considerably fewer circulating CD4+ T cell subsets than the non-excellent response group. Both the excellent response and non-excellent response groups had considerably lower circulating CD4+ T lymphocyte subsets 30 days after radioactive iodine treatment, but those of the excellent response group were still lower than those of the non-excellent response group. All circulating CD4+ T cell subsets in the excellent response group rose by varying degrees by the 90th day, but only Treg cell amounts increased in the non-excellent response group. Interestingly, in the non-excellent response group, we noticed a steady drop in Th1 cells. However, the bulk of circulating CD4+ T cell subsets between the two groups did not differ appreciably by the 90th day. Finally, we discovered that CD4+ T cell subsets had strong predictive potential, and we thus developed high-predictive-performance models that deliver more dependable prognostic information. In conclusion, in individuals with differentiated thyroid cancer, there is great variation in circulating immune cells, resulting in distinct treatment outcomes. Low absolute CD4+ T cell counts is linked to improved clinical outcomes as well as stronger adaptive and resilience capacities.